Etiology of community-acquired pneumonia in children and adults based on 2015–2022 bacteriological and molecular genetic studies - Victor I. Sergevnin; Marina V. Rozhkova; Kirill V. Ovchinnikov; Elena Zh. Kuzovnikova (Инфекция и иммунитет, 2023)
The data on etiology of community-acquired pneumonia (CAP) remain contradictory, which is often assessed only according to bacteriological studies coming to a conclusion about the low frequency of major main pathogenStreptococcus pneumoniaеisolation. At the same time, there are very few observations of parallel examination of patients with CAP simultaneously by bacteriological and molecular genetic methods. There are no observations on the etiology of CAP in the long-term dynamics. The aim of the work is to analyze the etiology of CAP in children and adults based on 2015–2022 bacteriological and molecular genetic studies. The etiology of pneumonia was assessed using the data on posterior pharyngeal wall washes from 418 children and 483 adults hospitalized with a primary diagnosis of CAP at two large Perm medical organizations in 2015–2022. The samples were examined by the bacteriological method and polymerase chain reaction using commercial test systems with the amplifier “CFX96” (Bio-Rad, USA). The results showed thatS. pneumoniaе, despite implementing decreed vaccinations against pneumococcal infection, it remains the leading causative agent of CAP in both children and adults. The 2015–2022 frequency of pneumococcal discharge according to bacteriological studies was 9.7 per 100 examined, according to molecular genetic studies — 48.5 per 100 examined among children and adults in the study area. According to 2021–2022 vs 2015–2017 bacteriological studies, the frequency ofStaphylococcus aureusexcretion among children increased significantly, andS. pneumoniaеincreased among adults. According to the results of molecular genetic studies among children and adults, no significant changes in the etiology of CAP were found. In 2021–2022, SARS-CoV-2-positive vs SARS-CoV-2-negative patients with CAP infected had higher rate of isolatedS. aureus,KlebsiellapneumoniaеandHemophilus influenzae, i.e., those pathogens whose number increased in the long-term follow-up observations.